Fabrication of graphite contamination free polycrystalline transparent MgAl2O4 spinel by spark plasma sintering using platinum foil. Issue 15 (15th November 2016) - Biswas, Papiya; Chakravarty, Dibyendu; Suresh, Madireddy Buchi; Johnson, Roy; Mohan, Mantravadi Krishna
Abstract: Discoloration due to graphite contamination in Spark Plasma Sintered (SPS) transparent magnesium aluminate (MgAl2 O4 ) spinel is a major problem, leading to poor transmission values. In an attempt to eliminate the graphite contamination due to the graphite punches and foil generally employed, in the present study the spinel powder was encapsulated in a platinum foil before subjecting to SPS. Properties of SPS samples with graphite foil and with platinum foil processed under identical conditions were compared. Unlike the graphite foil, the platinum encapsulated SPS sample is found to eliminate the graphite contamination. Further, the sample produced through platinum encapsulation exhibited close to theoretical transmission of 85% in 3–5 µm region without post SPS annealing, which is an essential step followed for elimination of graphite contamination. The study demonstrated for the first time, the use of platinum foil for obtaining the graphite contamination free SPS samples.